Farmers’ Participation in Irrigation Management and Influencing Factors in West Bengal - Golam Torab Ali; Souvik Ghosh (Indian Journal of Extension Education, 2018)
Farmers’ participation in management of minor irrigation systems through water user association (WUAs) has been attempted since 2012 in West Bengal. Present study was conducted covering 80 farmers, 40 each representing from river lift and groundwater lift irrigation command areas in Birbhum district of West Bengal. The perceptions of the farmers in both river lift and groundwater lift irrigation commands regarding different aspects of WUAs have not varied much. Farmers perceived performance of WUAs with respect to the water management as best in both types of irrigation system. The overall performance of WUAs in groundwater irrigation is perceived relatively better (2.90) as compared to river lift irrigation (2.83) on a 5-point continuum scale. Farmers’ participation with respect to water management activities is maximum in both river lift irrigation (67%) and groundwater irrigation (65%) with over all FPI value is 58 and 56.64 per cent, respectively. Stepwise multiple regression analyses revealed that farmers’ perceptions on irrigation service utility, social participation, caste and resource position have explained 69 per cent variations (R2=0.69) in the performance of WUAs in river lift irrigation and groundwater irrigation command areas. It is evident that WUAs performance is mainly influenced by the perceptions of farmers on utility of irrigation service as it alone explained 48 per cent variation (R2=0.48). Therefore, WUAs should focus on better irrigation management in their jurisdiction areas fulfilling the objective of more crops per drop.